"Inside out" - An exceptional intussusception - Daniel J. Kardos; Agnes Vojcek; Gabor Ottoffy; Bela Kajtar; Gabriella Mohay; Peter Vajda; Ede Biro (Elsevier, 2023)
Introduction: We present the first case of appendiceal intussusception associated with myeloid sarcoma in a young patient. Minimally invasive techniques used along the clinical course are highlighted. Case description: A 2.5-year-old boy was admitted after three weeks of COVID-19 infection with ongoing symptoms of MIS-C. Due to constipation, distended belly and vomiting, US was done which showed ileocolic intussusception. After unsuccessful hydrostatic reduction laparoscopic exploration was performed, where the vermiform appendix was found to be thickened and partially intussuscepted into the coecum. The ileocecal region was exteriorized transumbilically. After manual reduction of the intussusception, a long, thickened, fragile appendix was removed. Histopathology revealed myeloid sarcoma. Bone marrow investigation identified acute myeloid leukemia. During the oncological treatment, laparoscopic cholecystectomy was necessary due to cholecystitis and cholelithiasis. The child recovered uneventfully in terms of surgical complications, with good cosmetic result. Conclusion: No similar case in childhood was found in the English literature. Unusual symptoms and radiological findings of intussusception can conceal unexpected disorders. Minimally invasive technique offered advantages in the treatment of the presented patient and can be recommended to treat intussusception or cholelithiasis, if applicable, during an ongoing oncological treatment as well.